BAGELEN PASCA PERANG JAWA (1830-1950): Dinamika Sosial Politik dan Ekonomi di Bekas Wilayah Negaragung Kasultanan Mataram Islam (Vorstenlanden) - Himayatul Ittihadiyah (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
This paper aims at describing one of the Javanese Islam which is sociopoliticallyand economically may be cited as the most dynamic regions duringthe period of one century. Bagelen, the former territory "negaragung has beenamended several times of a changing system of administration and two times achange of economic policy. First, (1830-1870), this period is called as cultivationsystem (cultuurstelsel). After the signing of the political contract 27 September1830, as a result of the defeat of the Java War, there was the so-called'transitional villages', the release of the coastal areas of the power of Mataram,including "mancanegara" Bagelen which was originally a granary for theSultanate of Mataram both Surakarta and Yogyakarta later annexed by thecolonial government. Administratively, the period saw a shift from the"mancanegara", a local residency under the authority of the Dutch East Indiescolonial government, based in Batavia. The period saw a change in zoningthroughout the residency and the addition of new officers to guide and overseethe workings of the indigenous population in the implementation of forcedcultivation. This happens partly because of rapid population growth. Becausethe population is a potential resource then it can be harnessed to the interests offorced cultivation. Second, (1870-1950), in this period re-entering societyBagelen latest round, the period of liberal economic system, in this period theyhave to face the liberal patterns in various aspects of life, ranging from how tomake a living, facing the industrialization of the owners of both private andgovernment capital. At this period also administratively Bagelen be mergedinto the residency of Kedu (August 1, 1901). At the same time, as an Islamicsociety they also have to deal with an influx of new religions, namelyChristianity, a religion which at that time known as the religion of thecolonizers.